PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN PADA PELANGGARAN HAK CIPTA LAGU “LAGI SYANTIK”: STUDI PUTUSAN NOMOR: 910 PK/PDT.SUS-HKI/2020.JKT.PST - Wibowo, Nanang Prastiyo; Astutik, Sri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This research is entitled " THE JUDGE'S CONSIDERATIONS IN DECISIONING THE VERDICT ON COPYRIGHT INFRINGEMENT OF THE SONG "LAGI SYANTIK" (CASE STUDY Number: 910 PK/Pdt.Sus-HKI/2021.JKT.Pst". The writer is interested in this title because he examines more deeply the copyright infringement of the song "More Beautiful". with reference to the title, the author will examine it using normative legal research methods or what is commonly known as normative juridical. examine all laws and regulations that are related to ongoing legal issues. Conceptual approach, moving from the views and doctrines that develop in the science of law, researchers will find ideas that give birth to legal notions. Understanding of these views and doctrines is the basis for researchers in building a legal argument in solving legal issues at hand and a case approach that functions to study legal norms and principles applied in practicing law. In the case of a cover version of a song that does not meet the elements listed in Articles 43 and 44, this action is considered a form of copyright infringement. Copyright violations by the defendants in this case included making cover versions of songs, modifying songs, and recording them in the form of video clips.